Management of venous hypertension following arteriovenous fistula creation for hemodialysis access - Mittal, Varun (Indian J Urol, 2016)
INTRODUCTION: Venous hypertension (VH) is a distressing complication following the creation of arteriovenous fistula (AVF). The aim of management is to relieve edema with preservation of AVF. Extensive edema increases surgical morbidity with the loss of hemodialysis access. We present our experience in management of VH. METHODS: A retrospective study was conducted on 37 patients with VH managed between July 2005 to May 2014. Patient demographics, evaluation, and procedures performed were noted. A successful outcome of management with surgical ligation (SL), angioembolization (AE), balloon dilatation (BD) or endovascular stent (EVS) was defined by immediate disappearance of thrill and murmur with resolution of edema in the next 48–72 h, no demonstrable flow during check angiogram and resolution of edema with preservation of AVF respectively. RESULTS: All 8 distal AVF had peripheral venous stenosis and were managed with SL in 7 and BD in one patient. In 29 proximal AVF, central and peripheral venous stenosis was present in 16 and 13 patients respectively. SL, AE, BD, and BD with EVS were done in 18, 5, 4, and 3 patients, respectively. All patients had a successful outcome. SL was associated with wound related complications in 11 (29.73 %) patients. A total of 7 AVF were salvaged. One had restenosis after BD and was managed with AE. BD, EVS, and AE had no associated morbidity. CONCLUSIONS: Management of central and peripheral venous stenosis with VH should be individualized and in selected cases it seems preferable to secure a new access in another limb and close the native AVF in edematous limb for better overall outcome.